Effectiveness of Training program in removable partial prosthesis design in dental students of the stomatological internship - Caro Magni, Rosa (2021)
Objective: The objective of the present study was to determine the effectiveness of a training program in PPR design in students of the Stomatological Internship course at Faculty of Dentistry of the University of San Martin de Porres. Materials and Methods: The sample consisted of 70 students, a 20-question cognitive questionnaire and a procedural evaluation were taken for each one at 2 different moments, before and after carrying out a training program in PPR design. Results: It was found that there are statistically significant differences (p <0.001) between the initial and final evaluations of the cognitive and procedural competences in the PPR design. Conclusions: It is concluded that the PRP design training program is effective